Targeted Inhibition of cGAS/STING signaling induced by aberrant R-Loops in the nucleus pulposus to alleviate cellular senescence and intervertebral disc degeneration - Dan Wu; Chen Yan; Linhui Han; Fudong Li; Ximing Xu; Jingchuan Sun; Yong Cao; Kaiqiang Sun; Jiangang Shi; Yuan Wang (Journal of Nanobiotechnology)
Abstract Intervertebral disc degeneration (IVDD) is a significant contributor to chronic low back pain and disability worldwide, yet effective treatment options remain limited. Through integrative analysis of single-cell RNA-seq data from intervertebral discs (IVDs), we have firstly uncovered that the aberrant accumulation of R-Loops—a type of triple-stranded nucleic acid structure—can result in the cytoplasmic accumulation of double-stranded DNA (dsDNA) and activate cGAS/STING signaling and induce cellular senescence in nucleus pulposus cells (NPCs) during IVDD. Restoring the R-Loop state significantly mitigated both the activation of the cGAS/STING pathway and NPC senescence. Additionally, we identified ERCC5 as a critical regulator of the R-Loop state and cellular senescence. Thus, we developed an NPC-targeting nano-delivery platform (CTP-PEG-PAMAM) to deliver si-Ercc5 to the NP region of the IVDD. This approach aims to modulate the abnormal R-Loop state and inhibit the activation of cGAS/STING signaling in NPCs for IVDD treatment. CTP-PEG-PAMAM demonstrated excellent targeting capability towards NPCs and NP tissue, and achieved effective silencing of the Ercc5 gene without causing systemic organ complications. Both in vitro and in vivo experiments revealed that CTP-PEG-PAMAM-siERCC5 significantly inhibited cGAS/STING signaling activated by aberrant R-Loops, alleviated cellular senescence and promoting cell proliferation, thereby delayed IVDD in a puncture-induced rat model. In conclusion, the ERCC5-R-Loop-cGAS/STING axis in NPCs represents a promising therapeutic target for delaying IVDD, and the designed CTP-PEG-PAMAM/siRNA complex holds great potential for clinical application in the treatment of IVDD. Graphical abstract Targeted inhibition of cGAS/STING signaling induced by aberrant R-loops in the nucleus pulposus to alleviate cellular senescence and intervertebral disc degeneration